2020
DOI: 10.1177/0271678x19895245
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to capillary plugging can predict brain region specific vessel loss with aging

Abstract: Vessel loss in the aging brain is commonly reported, yet important questions remain concerning whether there are regional vulnerabilities and what mechanisms could account for these regional differences, if they exist. Here we imaged and quantified vessel length, tortuosity and width in 15 brain regions in young adult and aged mice. Our data indicate that vessel loss was most pronounced in white matter followed by cortical, then subcortical grey matter regions, while some regions (visual cortex, amygdala, thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 193 publications
(551 reference statements)
4
54
3
Order By: Relevance
“…On the other hand, the fact that blood contains cells results in its viscosity increasing dramatically at small diameters 35 , so that even small pericyte-mediated constrictions can have a large effect. Indeed, complete stalling of blood flow in capillaries can occur as a result of neutrophils (which are less distensible than red blood cells) becoming stuck at narrow parts of the vessel, for example near constricted pericytes [36][37][38] , and this could also transform a small constriction into a much larger reduction of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the fact that blood contains cells results in its viscosity increasing dramatically at small diameters 35 , so that even small pericyte-mediated constrictions can have a large effect. Indeed, complete stalling of blood flow in capillaries can occur as a result of neutrophils (which are less distensible than red blood cells) becoming stuck at narrow parts of the vessel, for example near constricted pericytes [36][37][38] , and this could also transform a small constriction into a much larger reduction of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the significance of capillary stalling in aging, stroke, Alzheimer's disease, polycythemia and thrombocythemia 3,4,5,6,11,21,22,23 . In fact, capillary stalling largely impacts on CBF, and cognitive functions can be improved by suppressing capillary stalling in Alzheimer's disease 6,24 .…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to reproduce these results in human AD patients. In wild-type mice, capillary block increases with ageing and can lead to vessels being pruned [ 159 ]. Remarkably, although modelling suggested that the increased block in AD would lead to a decrease of CBF of less than 5%, applying intraperitoneally a high concentration of an antibody to a neutrophil surface marker (Ly6G) led to a relief of capillary block, an increase of blood flow by 26–32% and improved memory.…”
Section: Capillary Block By Neutrophils and Clot Formation Also Reducmentioning
confidence: 99%